2022
DOI: 10.1016/j.trecan.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Redrawing therapeutic boundaries: microbiota and cancer

Abstract: The unexpected roles of the microbiota in cancer challenge explanations of carcinogenesis that focus on tumor-intrinsic properties. Most tumors contain bacteria and viruses, and the host's proximal and distal microbiota influence both cancer incidence and therapeutic responsiveness. Continuing the history of cancer-microbe research, these findings raise a key question: to what extent is the microbiota relevant for clinical oncology? We approach this by critically evaluating three issues: how the microbiota pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 107 publications
(185 reference statements)
0
13
0
Order By: Relevance
“…The role of cancer-related microorganisms has been widely discussed in cancer microbiome research, as they provide differential markers for cancer (i.e., diagnosis, causality, and treatment) ( Sholl et al., 2022 ); for instance, two Korean studies identified specific biomarkers to predict the severity of cervical diseases using a RFM ( Lee et al., 2020 ; Kang et al., 2021 ). Regarding the causal links between CC and vaginal microbiota, it is plausible to postulate that the vaginal microbiota may act as a cancer regulator during cervical tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of cancer-related microorganisms has been widely discussed in cancer microbiome research, as they provide differential markers for cancer (i.e., diagnosis, causality, and treatment) ( Sholl et al., 2022 ); for instance, two Korean studies identified specific biomarkers to predict the severity of cervical diseases using a RFM ( Lee et al., 2020 ; Kang et al., 2021 ). Regarding the causal links between CC and vaginal microbiota, it is plausible to postulate that the vaginal microbiota may act as a cancer regulator during cervical tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal in this paper is to examine particular issues that arise at the intersection of microbiome and cancer research. We see our work here as building on prior work by philosophers on tradeoffs, as well as contributing to recent philosophical discussions of both microbiome research and cancer research (e.g., Rondeau et al 2019;Sholl 2022;Laplane et al 2018Laplane et al , 2019, in the spirit of Longino's practice-centered philosophy of science (Longino 2016). Longino defends this approach because it allows for critical reflection on how evidence is brought to bear on various claims, as well as what assumptions or presuppositions are "involved in treating the data as evidence."…”
Section: Introductionmentioning
confidence: 94%
“…A series of studies on intratumoral microbes illustrates this trade-off between explanation and treatment, and its connection to the bigger issues at stake regarding causal attribution. Microbes are found in just about every micro-environment within our bodies, and tumors appear to be no exception (for a review of this literature, see Sholl et al 2022). Some researchers have sought to explore whether and how the tumor microbiome affects cancer development or response to treatment.…”
Section: Explanation Versus Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Increasing evidence indicates that the microbiota is strongly associated with human cancers, such as schistosomes and bladder squamous cell carcinoma [ 12 ]. BučevićPopović et al showed that 20% of malignant tumor tissues were infiltrated with microbes.…”
Section: Introductionmentioning
confidence: 99%